Urban food systems profile: Ghana - Amoah, Philip; Drechsel, Pay (International Water Management Institute (IWMI). CGIAR Initiative on Resilient Cities, 2024)
Over the last thirty years, Ghana’s population in towns and cities has more than tripled, from 4 million to nearly 14 million, exceeding growth in the rural areas. In fact, rural-urban migration is an important factor for urban growth. It is estimated that the urban population will reach over 70% by 2050, calling for fast and sustainable strategies for facilitating the main challenges deriving from rapid urbanization including urban food security and food system resilience against shocks. Several projects mapped urban foodsheds and the overall extent of specific city-region food systems. But not only food quantity, also food safety is at stake. A particular challenge for the farmers is widespread water pollution in urban area resulting in the contamination of irrigated vegetables. The largely informal nature of irrigated urban vegetable farming as well as the street food sector makes it difficult to regulate, promote or control compliance with food safety measures which are needed from farm to fork.